A basic study on hybrid systems for small race car to improve dynamic performance using lap time simulation - Kobayashi, Ikkei; Ogawa, Kazuki; Uchino, Daigo; Ikeda, Keigo; Kato, Taro; Endo, Ayato; Mohamad Heerwan, Peeie; Narita, Takayoshi; Kato, Hideaki
A hybrid vehicle is a vehicle with two or more power sources. We propose a hybrid system in which the engine torque converted by the transmission is combined with an electric motor torque. The proposed system reduces transmission because engine torque only acts during transmission. Furthermore, the proposed hybrid system’s simple structure uses lightweight chains and sprockets that can be laid out in various ways. The realization of the proposed hybrid system requires independent control algorithms for the two power systems, engine and electric motor, that take into consideration the state of the vehicle and the driver’s input; this system can be assumed to be a servo model system with multiple inputs and outputs and analyzed to obtain the optimal operation algorithm. To apply these controls to race cars, which are required to be fast, it is necessary to obtain the reference input, which is the optimal velocity and yaw angle while traveling the course of the servo system, and simulations of the competition track must be carried out. Therefore, the dynamic performance of the hybrid system was investigated by calculating the lap times on a given circuit using a quasi-steady-state method with low computational load and high prediction accuracy. In this study, the effects of changing the electric motor and final gear ratios on the driving performance of a rear-wheel-drive parallel hybrid system for optimization were investigated. The simulation results show that not only can the optimum settings be obtained by changing the final and electric motor reduction ratios on the evaluation circuit, but also that the optimum values vary across different speed ranges on different circuits.